Kontrowersje wokół promocji akademickiej w Stanach Zjednoczonych: rekonstrukcja debaty wokół Tenure = Controvercies around academic promotion in the United states: reconstrution of the debate over Tenure - Melosik, Zbyszko (1956- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the text is to present the American (and to some extent British) "variant" equivalent to habilitation, i.e. tenure: period in a researcher?s career decisive for his academic future. Gaining a tenure is crucial for the academic carrier at American universities.
Keywords: szkolnictwo wyższe; kariera naukowa; higher education; academic carrier